The Use of Supply Chain Risk Management Process (SCRMP) in Third-Party Logistics Industry: A Case Study in Indonesia - Pradita, Sintia Putri; Ongkunaruk, Pornthipa; Leingpibul, Thaweephan (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractGlobalization brought new opportunities to logistics providers worldwide, especially in the Mexico, Indonesia, South Korea, and Turkey (MIST) countries. However, this attractive opportunity also came with high risk due to the complexity of the global supply chain. Third-party logistics providers need to be prepared to minimize the risks by utilizing risk management to ensure a smooth supply chain operation. This case was conducted with a major Indonesian third-party logistics (3PL) provider, utilizing the Supply Chain Risk Management Process (SCRMP) to control and monitor all risks that can arise in the company. The structure of the method can be divided into four phases: risk identification, risk measurement/risk assessment, risk evaluation, and risk mitigation/contingency plans. The purpose of this research is to validate how the SCRMP concept performs in challenging contexts such as the Indonesian 3PL industry. The study also bridged the theoretical-practical gap by helping practitioners gain valuable insights to manage risks in the company and provided appropriate risk mitigation. The results showed that there are seven unacceptable risks requiring risk mitigation and control. Risk mitigation strategies were then recommended, based on the risks that were categorized as the most critical and unacceptable. The recommendation is expected to reduce the risks that occur in the Indonesian cold chain.Keywords: risk management, supply chain risk management process, third-party logistics providers